2003
DOI: 10.1021/la020159k
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Spheres Based on Mesostructured Lead Titanate with Amorphous Framework

Abstract: Hollow spheres of mesostructured lead titanate, denoted as PTM-1, have been prepared via a combined oil-in-water emulsion mediated and neutral amine supermolecular templated route. The variety of reaction temperatures and KOH concentrations indicates hollow spheres can be formed under a very critical condition. The structure and composition of the as-synthesized PTM-1 have been determined by powder X-ray diffraction, high-resolution transmission electron microscopy (HRTEM), energy-dispersive X-ray spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 66 publications
0
30
0
Order By: Relevance
“…Spherical structure is also favorable in terms of surface energy. Nanospheres are the most reported shape of amorphous materials in the last decade (see Table 1), and they can be composed of calcium carbonate (CaCO 3 ) [43][44][45][46][47], silicon (Si) [48][49][50][51][52], metals or their compounds [53][54][55][56][57][58][59][60][61]. CaCO 3 is abundant in the natural world, and a typical model system used to mimic the mineralization process of biominerals [43].…”
Section: Morphologies Of Amorphous Nanomaterials Spheresmentioning
confidence: 99%
See 2 more Smart Citations
“…Spherical structure is also favorable in terms of surface energy. Nanospheres are the most reported shape of amorphous materials in the last decade (see Table 1), and they can be composed of calcium carbonate (CaCO 3 ) [43][44][45][46][47], silicon (Si) [48][49][50][51][52], metals or their compounds [53][54][55][56][57][58][59][60][61]. CaCO 3 is abundant in the natural world, and a typical model system used to mimic the mineralization process of biominerals [43].…”
Section: Morphologies Of Amorphous Nanomaterials Spheresmentioning
confidence: 99%
“…Apart from the common amorphous nanospheres composed of CaCO 3 and Si, and amorphous nanospheres of some other compounds, such as Se [53], TiO 2 [54][55][56][57], Co-B alloy [58], FePO 4 [60] and zinc citrate [61], have also been prepared, generally by facile solution routes. Recently, Kuai et al [59] reported an interesting aerosol-spray-as- …”
Section: Morphologies Of Amorphous Nanomaterials Spheresmentioning
confidence: 99%
See 1 more Smart Citation
“…The resultant structures, which are called "colloidosome" , are hollow, elastic shells whose permeability and elasticity can be precisely controlled. M. M. Wu and co-workers 63) reported to prepare .…”
Section: Emulsion Template Methodsmentioning
confidence: 99%
“…Then the template is removed to form a cavity, leading to a hollow sphere structure [11,12]. The hollow spheres are generally fabricated by inorganic material of silica or non-silica oxides directly deposited on the surface of the polystyrene templates [13]. Another common method to fabricate microcapsules by the layer-by-layer (LBL) assembly [14,15], multilayer microcapsules with ultrathin wall thickness and tunable wall structures and properties has been fabricated.…”
Section: Introductionmentioning
confidence: 99%